Evaluación disergonómica en trabajadores de una empresa privada de Cusco, Perú: Dysergonomic evaluation in workers of a private company in Cusco, Peru - Olarte-Llave, Dina Rossy (2022)
Objective: To evaluate the ergonomic risk by type of work in workers of a private company located in the province of Espinar, Cusco-Peru. Materials and methods: Cross-sectional descriptive study. Thirty-four workers participated, of whom 27 were freight transport drivers and 7 were administrative workers. A questionnaire validated in content by expert judgment and internal validation was applied. For the evaluation of ergonomic posture, the REBA method applied to administrative personnel and the OWAS method applied to drivers were used, and the Ergo IBV software was used for processing. Results: Of the total number of participants, 79.41% (n=27) were male; with respect to the dimension (identification of health problems), 57.14% (n=4) of the administrative staff and 92.59% (n=25) of the driving staff had a fair and poor perception, respectively. With the REBA method, 88% (n=6) of workers presented high risk, and 13% (n=1) medium risk. Likewise, with the OWAS method, 70.37% (n=19) of the workers showed level 3 risk, and 29.63% (n=8) presented level 2 risk: In administrative workers and freight transport drivers there is a high risk of musculoskeletal injuries, directly affecting the cervical and dorsal lumbar region. Transport drivers are the most affected workers, therefore, it is suggested to take action measures in this regard. Keywords: Ergonomics; Occupational Exposure; Occupational Health; Peru (Source: MeSH, NLM).